Pharmacokinetics of Active Components From Guhong Injection in Normal and Pathological Rat Models of Cerebral Ischemia: A Comparative Study - Yu, Li; Wan, Hao-fang; Li, Chang; Yang, Jie-hong; Zhou, Hui-fen; Wan, Hai-tong; He, Yu (Frontiers in Pharmacology, 2018)
Background and Objectives Guhong Injection (GHI) is usually applied for the treatment of stroke in clinics. Aceglutamide and hydroxyl safflower yellow A (HSYA) were its key ingredients for brain protective effect. To investigate the pharmacokinetics of aceglutamide and HSYA under the pathological and normal conditions, the pharmacokinetic parameters and characteristics of middle cerebral artery occlusion (MCAO) and normal rats with same dosage of GHI were studied comparatively. Methods Twelve SD rats were divided into two groups, namely MCAO and normal groups. Both groups were treated with GHI in same dosage. Plasma samples at different time points were collected from jaw vein and subsequently tested by high-performance liquid chromatography (HPLC). Results After administration of GHI, both aceglutamide and HSYA were immediately detected in the plasma. 90% of aceglutamide and HSYA were eliminated within 3 h. For aceglutamide, there was statistically significant differences in the parameters including AUC(0–t), AUC(0-∞), AUMC(0-t), AUMC(0-∞), Cmax (P＜0.01) and Vz (P＜0.05) between the MCAO and normal rats. Meanwhile, compared with MCAO group, the values of AUC(0–t), AUMC(0-t), VRT(0-t) and Cmax (P＜0.01) about HSYA were significantly increased in normal group; the value of MRT(0-t) was significantly decreased in normal group. Conclusions The in vivo trials based on the different models showed that, the pharmacokinetic behaviors and parameters of aceglutamide and HSYA in GHI were completely different. These results suggested that the pathological damages of ischemia-reperfusion had a significant impact on the pharmacokinetic traits of aceglutamide and HSYA.